Jungleland a mysterious lost city, a WWII spy, and a true story of deadly adventure - Stewart, Christopher S (New York, NY Harper, 2013)
The author chronicles his present-day journey to find Ciudad Blanca, the legendary White City rumored to exist in the rain forests of Nicaragua's and Honduras' Mosquito Coast, following in the footsteps of the explorer and World War II spy Theodore Morde, who set out on the same journey on April 6, 1940
Includes bibliographical references (p. [261]-263)
1
Keywords: Morde, Theodore A -- 1911-1954 -- Travel -- Mosquitia (Nicaragua and Honduras); Stewart, Christopher S -- Travel -- Mosquitia (Nicaragua and Honduras); Adventure and adventurers -- Mosquitia (Nicaragua and Honduras) -- History -- 20th century; Explorers -- United States -- Biography; Geographical myths -- Mosquitia (Nicaragua and Honduras); Spies -- United States -- Biography; World War, 1939-1945 -- Secret service -- United States; Mosquitia (Nicaragua and Honduras) -- Description and travel; Mosquitia (Nicaragua and Honduras) -- History -- 20th century